JENIS-JENIS BAKAU DI DARUBA DAN WAYABULA, PULAU MOROTAI, MALUKU UTARA - Ahmad, Fasmi (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Inventarization on mangrove species in Daruba and Wayabula, Morotai Island were carried out in September 2005. The Result showed that in Daruba found three species of mangrove namely Rhizophora apiculata, Soneratia alba, Bruguiera gymnorhiza with Rhizophora apiculata as dominant species on tree category level. For belta criteria found three species namely Rhizophora apiculata, Bruguiera gymnnorhiza and Ceriops tagal with Rhizophora apiculata as dominant species. In Wayabula also found three species namely Rhizophora apiculata, Sonneratia alba and Rhizophora stylosa, with Rhizophora apiculata as dominant species. While on belta category found two species namely Rhizophora apiculata and Bruguiera gymnorhiza with Rhizophora apiculata as dominant species. Mangrove zone not only grow in coastal area, but also grow behind the coastline. Mangrove species in Morotai Island have the labile character, but stay relative in the good enough condition. That way, this condition is need remain to be defended and guarded against by a local resident activity trouble in order to be regional ecosystem of coastal area in Morotai Island can be sustained well. Region in Morotai Island is draw to be developed to become the natural recreation object, because owning interesting nature panorama.